Operation strategy and profitability analysis of independent energy storage participating in electricity market: A provincial case study in China - Gong, Jiawei; Xiong, Yun; Wu, Hao; Chen, Haoyong; Chen, Jianrun; Xiao, Dongliang (Frontiers in Energy Research, 2022)
The new energy storage has excellent value in the power system and can provide corresponding bids in various types of electricity markets. As the scale of new energy storage continues to grow, China has issued several policies to encourage its application and participation in electricity markets. It is urgent to establish market mechanisms well adapted to energy storage participation and study the operation strategy and profitability of energy storage. Based on the development of the electricity market in a provincial region of China, this paper designs mechanisms for independent energy storage to participate in various markets. Then, its current and future operation strategies by division time or capacity for participation in each type of market are analyzed, and the profitability under various scenarios is calculated. Finally, based on the calculation results, the theoretical analysis basis for developing independent energy storage in the province and the policy formulation of participation in the market is provided.